Husband and Wife Relationship of Early Marriage in Tangga Ulin Village (According to the Review of the Book of Uqud Al-Lujain Fi Bayan Huquq al-Zaujain) - Akhmad Sofyan; Risma Monirah (Ulumul Syar'i : Jurnal Ilmu-Ilmu Hukum dan Syariah, 2020)
Early marriage is a marriage that is carried out under the age specified by law. Usually, couples who do early marriages are very susceptible to disputes that result in divorce. The researcher wants to reveal, about the relationship pattern of married couples who carry out early marriages in Tangga Ulin Village, Hulu Sungai Utara Regency, where in that village there are many scholars and religious leaders who of course teach the book ‘Uqūd al-Lujain fi Bayān Huqūq al-Zaujain. In addition, the researcher wants to know the review of the book ‘Uqūd al-Lujain fi Bayān Huqūq al-Zaujain on the relationship patterns of husband and wife who carry out these early marriages. This research uses qualitative research with a normative empirical approach. The result of this research is The husband and wife relationship of the perpetrators of early marriage in Tangga Ulin Village applies a husband and wife relationship pattern that is not bound (flexible), in carrying out their respective rights and obligations to help and derstand each other between partners, so that they can ease the work and responsibilities that exist in their household. Then, according to the book ‘Uqūd al-Lujain fi Bayān Huqūq al-Zaujain especially the section "wives are encouraged to realize that they are like slaves to their husbands." However, in its application, it applies a pattern of mutual help and understanding (flexible) relationships. Thus, it is hoped that divorce will not occur again due to early marriage.